THE EFFECT OF EASE OF USE, RISKS TOWARDS CONSUMER DECISIONS WHEN SHOPPING ONLINE - Suleman, Dede; Dedi Suharyadi; Sofyan Marwansyah; Susan Rachmawati; Sri Rusiyati; Sabil Sabil (Dinasti Publisher, 2020)
The presence of various alternative shopping places makes consumers choose one of the available shopping places. Therefore this study aims to analyze the relationship between ease and risk of consumer decisions to buy fashion products, especially in online retail. the population in this study is large and the number is not known with certainty, so in the non probalitiy research that is using sampling quota sampling techniques with survey methods with a total sample of 100 respondents from the city of Jakarta with criteria respondents aged over 18 years in the area of DKI Jakarta and have bought products online. The results of the study stated that ease of use has a significant influence on consumer decisions. While the risk turns out to influence consumer decisions in shopping online. The results of this study can be another reference for further research.